2011
DOI: 10.1016/j.amjcard.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Bosentan for Pulmonary Arterial Hypertension in Adults With Congenital Heart Disease

Abstract: Time to extubation, maximum vasoactive-inotropic score, and length of hospital stay were selected as the secondary outcome variables.Compared with patients in whom the PDA was left open, patients with a surgically closed arterial duct had a higher incidence of resuscitation events (29.0% vs 0%, P = 0.0012), reinterventions (35.5% vs 3.2%, P = 0.0013), and higher early hospital mortality (9.7% vs 0%, P = 0.038). Time to extubation and length of hospital stay did not differ between the 2 groups (P = 0.16 and 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…The BREATHE-5 (Bosentan Randomised Trial of Endothelin Antagonist-5) trial and its long-term open-label extension study demonstrated the benefit of bosentan in patients with Eisenmenger's syndrome in terms of significant improvements in exercise capacity, haemodynamics and functional class compared with placebo, independently of the location of the septal defect [42][43][44]. Data from a number of studies have since confirmed these benefits in the longer term in patients with PAH-CHD and specifically in patients with Eisenmenger's syndrome [45][46][47][48][49][50]. Importantly, treatment with bosentan has been shown not to reduce systemic arterial blood oxygen saturation over short- [42] and long-term treatment [47], demonstrating that it had no negative effect on the overall shunt.…”
Section: Management Of Pah-chd With Pah-specific Therapiesmentioning
confidence: 77%
See 1 more Smart Citation
“…The BREATHE-5 (Bosentan Randomised Trial of Endothelin Antagonist-5) trial and its long-term open-label extension study demonstrated the benefit of bosentan in patients with Eisenmenger's syndrome in terms of significant improvements in exercise capacity, haemodynamics and functional class compared with placebo, independently of the location of the septal defect [42][43][44]. Data from a number of studies have since confirmed these benefits in the longer term in patients with PAH-CHD and specifically in patients with Eisenmenger's syndrome [45][46][47][48][49][50]. Importantly, treatment with bosentan has been shown not to reduce systemic arterial blood oxygen saturation over short- [42] and long-term treatment [47], demonstrating that it had no negative effect on the overall shunt.…”
Section: Management Of Pah-chd With Pah-specific Therapiesmentioning
confidence: 77%
“…Data from a number of studies have since confirmed these benefits in the longer term in patients with PAH-CHD and specifically in patients with Eisenmenger's syndrome [45][46][47][48][49][50]. Importantly, treatment with bosentan has been shown not to reduce systemic arterial blood oxygen saturation over short- [42] and long-term treatment [47], demonstrating that it had no negative effect on the overall shunt. Treatment with bosentan has also been shown to have a positive long-term effect on QoL, a particularly important consideration for Eisenmenger's syndrome patients [49].…”
Section: Management Of Pah-chd With Pah-specific Therapiesmentioning
confidence: 80%
“…Assessments were performed before and after 8-week combined resistance and aerobic exercise training. A subset of our type 2 diabetes participants (n=8) also received a dual endothelin-receptor blocker (Bosentan, Actelion Pharmaceuticals) during the first 4 weeks represented 62.5 mg taken orally twice per day, followed by four weeks of 125 mg twice daily (Monfredi et al 2011). A priori we expected no impact of this intervention on arterial wall thickness and, to increase the power of our study, we have combined these subjects with type 2 diabetes patients that performed exercise training only (n=12).…”
Section: Experimental Measuresmentioning
confidence: 99%
“…In addition, a follow-up study showed further improvement in functional class and the 6-minute walk distance in these patients. 43) There were no significant differences in efficacy between subgroups of patients with ASD, VSD, or both. Long-term follow-up found improvements in functional class and exercise tolerance lasting at least 2 years.…”
Section: How Does Pulmonary Vasodilator Therapy Affect Outcomes In Pamentioning
confidence: 99%